Vascular complications in steroid treated patients undergoing transfemoral aortic valve implantation. Issue 2 (23rd May 2015) - Fink, Noam; Segev, Amit; Barbash, Israel; Bogdan, Andrada; Hamdan, Ashraf; Mazin, Israel; Maor, Elad; Hay, Ilan; Guetta, Victor; Fefer, Paul
Abstract : Objective: To assess the rate of Vascular complications in steroid treated patients undergoing transfemoral aortic valve implantation (TAVI). Background: Steroid therapy has been associated with increased post‐surgical bleeding. Vascular complications are a major concern in patients undergoing TAVI. However, the effect of corticosteroids on vascular complications has not been assessed in these patients. Methods: We conducted a retrospective analysis of 220 consecutive patients undergoing transfemoral TAVI at our institute between 2009 and 2013. Patients who were on steroids at the time of the procedure ( n = 25) were compared with those who were not ( n = 195). Results: Baseline characteristics between groups were similar except for greater incidence of chronic renal failure (52 vs. 25%, P = 0.05) and lower left ventricular ejection fraction (50.3 vs. 55.8%, P = 0.037) in the steroid group. The rate of procedural success and nonvascular complication were similar in both groups with the exception of more temporary AV block in the steroid group (24 vs. 8%, P = 0.016). Patients treated with steroids had significantly more minor vascular complication (44 vs. 23%, P = 0.024), and significantly more femoral artery stenosis (16 vs. 5%, P = 0.036), occlusion (8 vs. 1%, P = 0.014), need for femoral artery percutaneous transluminal angioplasty (PTA) (32 vs. 12%, P = 0.009), and femoral artery PTA or stenting (32% vs. 15%, P = 0.031). On multivariate analysis steroid treatment was the only predictor of minor vascular complications (RR=2.65, 95% CI 1.04‐6.8, P = 0.042). Conclusions: Concurrent corticosteroid treatment is associated with a higher rate of minor vascular complication following transfemoral TAVI. Operators should be aware of this risk when assessing patients for the procedure. © 2015 Wiley Periodicals, Inc.